First record of the spider family Hersiliidae (Araneae) from the Mesozoic of Europe (Bakony Mts, Hungary). (March 2022) - Szabó, Márton; Hammel, Jörg U.; Harms, Danilo; Kotthoff, Ulrich; Bodor, Emese; Novák, János; Kovács, Kristóf; Ősi, Attila
Abstract: An adult male Hersiliidae spider is described from amber that originates from the Upper Cretaceous (Santonian) Ajka Coal Formation (Ajka-Csingervölgy, Hungary), the so-called ajkaite. The spider has elongate posterior spinnerets and a short third pair of legs III, both characteristics of the family, but differs from all known Mesozoic (discovered in burmite) and fossil and Recent European representatives of Hersiliidae so that a new genus and species name is proposed for Hungarosilia verdesi gen. et sp. nov. The new taxon is distinguishable by the following unique combination of characters: pro- and opisthosoma nearly circular in dorsal view; posterior spinnerets with a distal article more than three times longer than the basal article; pedipalpal tibia and patella short and stout but pedipalpal femur as long as the cymbium, cymbium egg-shaped and without cymbial apophysis; bulbus of circular shape in ventral view and slightly flattened is lateral view. The fossil represents the first record of Hersiliidae from the Mesozoic of Europe and establishes the second record of this family in the Mesozoic Era. The estimated paleoclimate and paleoflora of the Ajka coal sub-basin correspond well with habitat preferences of Recent relatives that are often arborical and found in association with tree bark. Overall, our findings highlight the importance of a neglected amber type, the ajkaite, for documenting and studying the European arthropod fauna during the Mesozoic.